Laparoscopic excision of a lymphangioma of the cystic duct. Issue 4 (November 2014) - Natoudi, Maria; Tsamis, Dimitrios; Zoumpouli, Christina; Leandros, Emmanouil; Albanopoulos, Konstantinos
Abstract Lymphangiomas are benign tumors that originate from malformations of the lymphatic vessels. They are rarely seen in adults and are extremely rare in the cystic duct. Herein, we report the case of a 48‐year‐old woman who presented with a cystic lymphangioma that originated in the cystic duct and was excised laparoscopically. Preoperative imaging revealed the cystic and benign nature of the lesion. Laparoscopic abdominal exploration and excision of the 10‐cm cystic lymphangioma were performed. Four trocar sites were used, and the excision was achieved using clips and electrocautery. The laparoscopic excision of these benign masses is safe and efficacious in experienced hands. This procedure requires preoperative planning and must be individualized.